The Odyssey of Ibn Battuta : uncommon tales of a medieval adventurer - Waines, David; Ibn Batutta , 1304-1377 (I.B. Tauris, 2010)
"Ibn Battuta was, without doubt, one of the world's truly great travellers. Born in fourteenth-century Morocco and contemporary of Marco Polo, Ibn Battuta has left us an account in his own words of his remarkable journeys throughout the Islamic world and beyond. ... David Waines discusses [Ibn Battuta's work], life, and times ..."-- Jacket.